Diários e ficção: as escritas entretecidas de Erico Verissimo - Manna, Lucia Helena Sgaraglia (2011)
A volta do gato preto, the narrative of Brazilian writer Erico Verissimo s second trip to the United States in 1943, was structured in the form of diaries. The twoyear sojourn in California, described in these diaries, enabled the writer to reexamine his cultural roots from his condition as a foreigner, in contrast with the Other. After his return to Brazil in 1945, Verissimo soon started the O tempo e o vento trilogy, to which contributed the fragmentary texts of the Californian diaries. Amidst an identity crisis, one of the novel s characters, Floriano Cambará, the writer s alter ego, describes the life of his family and the history of his native state, Rio Grande do Sul.